Experiencia y autoridad en el Contra académicos de san Agustín - Pascual, L.C., Fernando (Alpha Omega, 2002)
Summary: St. Augustine’s Contra academicos invites us to meditate on the roads that man uses to joumey towards truth, truth that is a source of deep joy and the goal of authentic philosophy. This article underlines the importance for St. Augustine of experience, reason, authority and faith as means to the fullness of truth. lt also describes the dangers that Augustine sees in the different methods employed.